2017
DOI: 10.1371/journal.pone.0183248
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of non-O157 Shiga toxin-producing Escherichia coli from beef carcasses, cuts and trimmings of abattoirs in Argentina

Abstract: Several foods contaminated with Shiga toxin-producing Escherichia coli (STEC) are associated with human diseases. Some countries have established microbiological criteria for non-O157 STEC, thus, the absence of serogroups O26, O45, O103, O104, O111, O121, and O145 in sprouts from the European Union or ground beef and beef trimmings from the United States is mandatory. While in Argentina screening for O26, O103, O111, O145 and O121 in ground beef, ready-to-eat food, sausages and vegetables is mandatory, other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 50 publications
4
29
1
Order By: Relevance
“…For this reason, chances of humans becoming infected by these strains are large, indicating the importance of this serogroups to public health. 5 Therefore, the O116 serogroup observed in the present study is relevant due to the fact that it is often associated with severe human disease. Furthermore, the strain with the flagelar antigen H18 which contains the stx 2 but not the eae gene, has also shown frequent association with infections in animals.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…For this reason, chances of humans becoming infected by these strains are large, indicating the importance of this serogroups to public health. 5 Therefore, the O116 serogroup observed in the present study is relevant due to the fact that it is often associated with severe human disease. Furthermore, the strain with the flagelar antigen H18 which contains the stx 2 but not the eae gene, has also shown frequent association with infections in animals.…”
mentioning
confidence: 79%
“…Several studies have analyzed STEC and EPEC, and their virulence in humans, 4 cattle, 5 sheep, 6 pigs, 7 and buffaloes. 8 However, only a few studies have analyzed the presence of STEC and EPEC in fish 9 , 10 and, of these, none has detected presence of adhesion and ESBL genes.…”
mentioning
confidence: 99%
“…Beef trimmings are pieces of meat remaining after steaks, roasts and other cuts are removed, and which are often used to make ground beef or hamburgers. A study evaluating the prevalence of non-O157 STEC in beef carcasses, cuts and trimmings from eight Argentinean abattoirs showed that 5.8% pools of carcass and cut samples and 7% pools of beef trimming samples were positive for non-O157 STEC [3]. These findings demonstrated that beef trimmings were an important vehicle of STEC and reflected the importance of applying antimicrobial interventions.…”
Section: Introductionmentioning
confidence: 97%
“…Absence of E. coli O157:H7 and non‐O157 STEC (mainly O26, O103, O111, O145, and O121 serogroups) strains in ground beef sold at retail markets is mandatory in Argentina (Argentinean Food Code, ). However, during 2015, 337 HUS cases were reported, and even though E. coli O157:H7 was the predominant serotype isolated from patients, non‐O157 STEC strains were responsible for 25.1% of STEC infections (Brusa et al, ). Consumption of undercooked beef has been identified as a major risk factor, and meat products of different animal origin have been investigated as the most probable STEC transmission vehicles in this country (Brusa et al, ; Chinen et al, ; Jure et al, ).…”
Section: Introductionmentioning
confidence: 99%